Experiments in measuring dynamic hydrostatic constitutive properties of soft materials. (September 2021) - Fox, C.; Kishore, S.; Senol, K.; Shukla, A.
Abstract: An experimental investigation is conducted to develop, analytically model, and test a novel facility to obtain the dynamic hydrostatic constitutive properties and behavior of soft materials. The novel facility is an underwater shock tube consisting of two aluminum sections and an optically-clear acrylic section in between, all filled with water. A striker-piston configuration is used to provide an axial shock loading to one end of the assembly. Dynamic pressure sensors provide pressure data along the entire length of the assembly, including at the specimen location in the acrylic section. 3D Digital Image Correlation (DIC) is used in conjunction with high-speed photography to provide full-field deformation data of the specimen to obtain volumetric strain. The mismatch in acoustic impedance between the aluminum and the acrylic sections causes a reduction in the amplitude of the pressure pulse by 33%. The pressure pulse also undergoes appreciable dispersion in the acrylic section. Fluid-structure interaction (FSI) models are considered and applied to understand the dispersion characteristics of the axially propagating pressure pulse. The dynamic hydrostatic constitutive response of closed-cell polyvinyl chloride (PVC) foam is obtained at a volumetric strain rate of 100s −1 . The bulk modulus at this strain rate for H130 PVC foam is measured to be 106.97 ± 3.11MPa. This is more than double that of the quasi-static (0.001s −1 ) value of 46.71 ± 1.91MPa, indicating a strong effect of strain rate on the material's response. The buckling pressure is also found to be strain rate dependent, with the dynamic buckling occurring at 3.09 ± 0.12MPa and quasi-static buckling occurring at 1.39 ± 0.17MPa. Highlights: Dynamic hydrostatic constitutive properties of soft materials are measured. An underwater shock tube facility with a striker-piston assembly is used. Dynamic pressure sensors and 3D Digital Image Correlation provide constitutive data. Fluid-structure interaction models are developed understand the pressure profile. Closed-cell polyvinyl chloride foams are tested at a strain rate of 100s −1 . The dynamic bulk modulus and dynamic hydraulic crush point are obtained.